Integrasi antara Sains Modern dan Nilai-Nilai Islam dalam Menghadapi Tantangan Kehidupan Kontemporer - Faizah Nuswah; Syafiin Mansur (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The rapid development of modern science and technology has brought major transformations to various aspects of human life, including education, communication, economics, health, and social interaction. Nevertheless, this progress often creates a gap between scientific advancement and spiritual or moral values, particularly when viewed from an Islamic perspective. This study aims to analyze the relationship between modern science and Islamic teachings, while also exploring relevant forms of integration between the two in responding to contemporary life challenges. The research employs a qualitative approach through a comprehensive literature review of books, scientific journals, and other academic sources related to science and Islam. The findings indicate that Islam is fundamentally not opposed to science; instead, Islamic teachings encourage critical thinking, intellectual development, and the pursuit of knowledge for the benefit of humanity. Furthermore, the integration of scientific knowledge and Islamic values is considered essential in maintaining balance between technological progress, ethical responsibility, and human morality. Therefore, continuous and contextual efforts are needed to harmonize science and religion so that both can contribute optimally to the development of a more humane, ethical, and spiritually grounded civilization.